The big book of stars & planets - Kerodo, Robin (Hamlyn London, 1992)
This is one of a series of information books which attempt to take a fresh look at a variety of subjects that fascinate children. The books include illustrations and cut-away artwork to help children with their school project work or as background reading at home.